Basics fire safety - Helmerking, Diana (Birkhäuser, 2020)
Fire safety is an important part of building design. It consists of measures to prevent fires from starting, to facilitate the rescue of individuals in a burning building, and to help firefighters contain a blaze. The book explains the general concepts and fundamental issues of fire safety in building design beyond the particulars of local building regulations.- Resumé vydavatel
Keywords: požární bezpečnost staveb; fire safety of buildings; elektronické knihy; monografie; electronic books; monographs